Applicability of lignin polymers for automobile brake pads as binder and filler materials and their performance characteristics. Issue 4 (10th February 2020) - Park, Jeesu; Hwang, Hyewon; Kim, Jae Young; Choi, Joon Weon
ABSTRACT: We present environmentally friendly brake pads produced with three different types of lignin, soda lignin (SL), sulphuric acid lignin (SAL) and heat-treated SAL (HL), as frictional materials to replace phenol formaldehyde resin (PFR, binder) and cashew nut shell liquid (CNSL, filler) in commercial automobile brake pad. Then the performance characteristics of the lignin-added brake pads were tested and compared using several fundamental tests. The results showed that lignin-added brake pads adhered to the SAE standard (0.25) for friction coefficient, which is the primary contributor to the performance of a braking system. In particular, the replacement of PFR with SL demonstrated a better friction coefficient than did replacement with SAL or HL, reaching up to 0.6. On the other hand, when lignin was substituted for CNSL as filler, HL-added brake pads showed a significant improvement in wear resistance of 0.12 g (dust generation) compared to SL and SAL, which had a resistance of approximately 0.25 g. GRAPHICAL ABSTRACT: